Fertility managment in testicular cancer: the need to establish a standardized and evidence‐based patient‐centric pathway. (27th July 2018) - Moody, Jemma A.; Ahmed, Kamran; Yap, Tet; Minhas, Suks; Shabbir, Majid
Abstract : Objectives: The aim of the present paper was to determine the impact of testicular cancer (TC) and its treatments on fertility and to review the current management options for the infertile patient with TC, both before diagnosis and after treatment, with the aim of providing practical recommendations to update contemporary guidelines and standardize clinical practice. Patients and Methods: Searches were conducted for relevant articles on Pubmed and Google Scholar between 2000 and 2017, with additional articles sourced from reference lists of included publications. Results: At time of diagnosis, 6–24% of patients with TC were reported to be azoospermic and 50% oligozoospermic. Without conducting semen analysis at diagnosis, these patients cannot be identified and may be at further risk of subfertility. Gonadotoxic therapies cause an overall decrease in male fertility by 30% and there is currently no method to predict which patients will become azoospermic after treatment. Patients with larger, more invasive tumours, however, are at greater risk of infertility from local tumour effects, and are also more likely to undergo several different type of therapy, which has further detrimental effects on conception rates. Most treatment‐induced infertility recovers 2 years post‐treatment, but paternity can be delayed during a couple's peak reproductive years. Semen cryopreservation remains the procedure of choice in preserving fertility, but the service is underused, with only 24% of patients banking sperm. Microdissection testicular sperm extraction (microTESE) at the time of orchidectomy (onco‐microTESE) is a successful infertility treatment option for those found to be azoospermic or severely oligozoospermic at diagnosis, while microTESE may still retrieve sperm in azoospermic patients after chemotherapy. Conclusion: The underutilisation of semen analysis and sperm cryopreservation results in the failure to identify the azoospermic or severely oligozoospermic patient at diagnosis who may benefit from fertility‐preserving procedures, for example, onco‐microTESE at the time of orchidectomy. Fertility preservation and counselling needs to be broached earlier in the TC treatment pathway and made a greater priority. Given the advances in treatment, more patients with TC are surviving and looking to return to a normal life. Preserving their future fertility plays an important role in achieving this.